The Tolerance Trap : How God, Genes, and Good Intentions are Sabotaging Gay Equality - Walters, Suzanna Danuta (Book collections on Project MUSE., 2014)
From Glee to gay marriage, from lesbian senators to out gay Marines, we have undoubtedly experienced a seismic shift in attitudes about gays in American politics and culture. Our reigning national story is that a new era of rainbow acceptance is at hand. But dig a bit deeper, and this seemingly brave new gay world is disappointing. For all of the undeniable changes, author Walters argues, the plea for tolerance has sabotaged the full integration of gays into American life. Same-sex marriage is unrecognized and unpopular in the vast majority of states, hate crimes proliferate, and even in the much vaunted "gay friendly" world of Hollywood and celebrity culture, precious few stars are openly gay. She maintains that we are not "almost there," but on the contrary have settled for a watered-down goal of tolerance rather than a robust claim to full civil rights. After all, one "tolerates" unpleasant realities: medicine with strong side effects, a long commute, an annoying relative. Tolerance is not the end goal, but a dead end.--Publisher information.